Enfrentamento da desinformação por meio do desenvolvimento das competências informativas na biblioteca escolar - Campos, Erica Silva (2024)
Disinformation, whether produced through manipulation or manufactured with false and/or out-of-context data, has become a problem of national and international proportions, being researched by scientists, professionals and institutions in various parts of the world, demanding confrontation in order to contain the advancement of its spread. The current moment of proliferation of desinformation demands information and reading skills to distinguish between coherent and fallacious information, amidst the diversity of information content available. At this juncture, the education of children and adolescents to use information represents great social relevance, contributing to the formation of critical subjects in the processes of searching, evaluating and using information, since these subjects are producers and consumers of information in the mediatized society. Inserted in a time of transformation due to the ease of searching and retrieving information in contemporary society, the school needs to commit to training critical subjects with skills to appropriate information in physical and digital environments, which places the school library as a face-to-face space that is potentially affected by new technologies, requiring critical and ethical informational practices, which can act on the development of the skills of members of the school community. Therefore, this research had the general objective of investigating the contribution of the school library in the formation of critical subjects in contemporary society, through practices that contribute to the improvement of information skills aimed at combating desinformation. To this end, participatory and bibliographical research procedures were adopted in the context of a qualitative, exploratory and descriptive study regarding the objectives. Data collection took place through survey and analysis of literature concerning the topic and application of questionnaires involving teachers and students from a municipal elementary school in the Municipality of Vila Velha in the State of Espírito Santo. The questionnaires were based on international standards for the development of information skills (IFLA/UNESCO, 2007), and also in literature in the area of Information Science. With the results, the strategic potential of the school library in developing information skills for the training of critical readers is evident. The study demonstrates that the school library has assumed its pedagogical function within the school, and, through educational actions and literary practices, has been contributing to the development of information skills in elementary education, improving skills, knowledge and attitudes in the field of information and of critical reading. However, we draw attention to the need for specific actions aimed at improving and/or developing information knowledge and skills to combat disinformation, with the interrelated development of information skills (Information Competence, Reading Competence, Digital Competence, Infocommunication Competence and Infomedia Competence) providing students with the opportunity to enjoy the information environment with reliability, enabling digital natives to search for relevant content in hybrid environments, learning to evaluate and ethically use the information